Optimalisasi Pendayagunaan Zakat melalui Program Beasiswa Sahabat Pendidikan Ulil Albab : Optimization of Zakat Utilization through the Ulil Albab Educational Companion Scholarship Program - Jambak, Arya Neta Adinda; Nasution, Yenni Samri Juliati (Litera Academica Publishing, 2024)
Zakat is one of the important pillars in Islam that plays a vital role in enhancing social welfare and alleviating the burdens of underprivileged communities. In the context of Indonesia, the management of zakat is regulated by the Zakat Management Agency (BAZ) and Zakat Institutions (LAZ) based on Law Number 23 of 2011. Although zakat is generally consumptive in nature, it is important to develop productive zakat that can support business capital and education. With only 6.52% of Indonesia's population pursuing higher education, the utilization of zakat for scholarships and educational infrastructure becomes crucial. The Zakat Institution Ulil Albab has implemented a scholarship program for academically talented but financially disadvantaged students, focusing on both academic development and moral character. This research aims to examine the effectiveness of zakat management in improving access, quality, and equity in education in Indonesia, as well as to formulate a more efficient and impactful zakat management model. This study employs a qualitative descriptive method, with data collected through interviews, observations, and document studies. Based on the research findings, it was discovered that the scholarship program managed by the Zakat Institution Ulil Albab has a significant impact on its recipients, both in terms of education and the development of soft skills for the students benefiting from this program.